Hexagonal boron nitride hollow capsules with collapsed surfaces：Chemical vapor deposition with single-source precursor ammonium fluoroborate - 李肖鹏 张军 郁超 刘晓喜 Saleem Abbas 李杰 薛彦明 唐成春 (Chinese physics B, 2016)
SBA-15（mesoporous SiO2） is used to stabilize and transfer F-in the NH4BF4 CVD reaction for the first time, and a large-scale crystalline h-BN phase can be prepared. We successfully fabricate hollow h-BN capsules with collapsed surfaces in our designed NH4BF4 CVD system. Optimum temperature conditions are obtained, and a detailed formation mechanism is further proposed. The successful SBA-15-assisted NH4BF4 CVD route is of importance and enriches the engineering technology in the h-BN single-source CVD reaction.